Women’s Health Tracks for Internal Medicine Residency Programs: Current State and Best Practices - Rebeca Ortiz Worthington; Jennifer Rusiecki; Molly Fisher; Jaya Mehta; Swati Shroff; Mindy Sobota; Sarah Tilstra; Melissa A. McNeil (Journal of Women's Health, 2026)
Background: Women’s health (WH) is recognized as a core competency in internal medicine (IM) residency programs, yet residents report inadequate training and low comfort across WH topics. Some IM residencies have established tracks to meet this need, but no comprehensive review of their implementation and structure exists. We describe the current state and best practices for WH tracks in IM residency programs. Methods: We reviewed current WH tracks within U.S. categorical IM residency programs. Program websites were reviewed for information on leadership, clinical focus, and requirements. Track leaders were contacted for verification and additional information. Four well-established tracks were selected as case studies. Results: There are 12 WH tracks in IM residencies. Key common elements among successful tracks include regular educational sessions, dedicated clinical training blocks, at least two core WH practicing general IM faculty, faculty salary support, and administrative support. Clinical training blocks consistently include focused primary care experiences and subspecialist clinical partnerships. Educational activities often include both faculty- and resident-led sessions. Resident participation ranges from 0 to 8 per postgraduate year. Successful tracks cultivate community through social events and mentorship. Challenges include financial and administrative support and recruiting and retaining core faculty. Conclusions: WH tracks offer a solution to IM training limitations. Successful tracks are characterized by consistent clinical training, didactic education, and mentorship. They effectively build community, establish robust primary care training, support residents across various career interests, and cultivate strong faculty teams and subspecialist partnerships. Dedicated faculty time and administrative support are key to sustained success and growth.